The narrative of special education in Sweden: History and trends in policy and practice. Issue 4 (3rd July 2016) - Hjörne, Eva
ABSTRACT: Access to public education that provides equal opportunities for all is a democratic right for every person living in Sweden. In addition, every child should as far as possible be included in the mainstream school. An official story that is taken for granted in Sweden is that an extremely low proportion of children are in need of special support, since there is no categorisation system in the official statistics. However, the results from the interviews of a number of key informants in the Swedish school system and several research studies show the opposite; the proportion of children categorised in practice as being in need of special support has increased dramatically, especially the group of children assigned with neuropsychiatric diagnoses for example Attention Deficit Hyperactivity Disorder. This paper explores the implications of growing segregation of children with special educational needs for the idea of an inclusive education system.